Effectiveness of Emotion-Focused Therapy on Behavioral Emotion Regulation and Marital Stress in Married Women - Poursheykhian, Soudabeh; Samkhaniani, Eshagh (Psychology of Woman Journal, 2025)
Objective: The present study aimed to determine the effectiveness of Emotion-Focused Therapy (EFT) on behavioral emotion regulation and marital stress in married women.Methods and Materials: This research employed a semi-experimental and applied methodology, utilizing a pre-test–post-test design with a control group. The statistical population included all married women who visited counseling centers in Ramsar County during the first half of 2025. A total of 30 participants were selected using purposive sampling and were randomly assigned to experimental (n = 15) and control (n = 15) groups. The research instruments included the Behavioral Emotion Regulation Questionnaire by Garnefski and Kraaij (2019) and the Stockholm Marital Stress Questionnaire developed by Orth-Gomer et al. (2000). Data analysis and hypothesis testing were conducted using multivariate analysis of covariance (MANCOVA) and univariate analysis of covariance (ANCOVA).Findings: The results revealed a significant difference between the intervention and control groups in terms of the mean scores of behavioral emotion regulation and marital stress (p < .001).Conclusion: The findings favored the experimental group. Overall, the results indicated that Emotion-Focused Therapy led to a reduction in marital stress and an improvement in behavioral emotion regulation among married women.